2010
DOI: 10.1111/j.1600-0609.2010.01541.x
|View full text |Cite
|
Sign up to set email alerts
|

Male gender is an adverse prognostic factor in B-cell lymphoma patients treated with immunochemotherapy*

Abstract: Male gender is an adverse prognostic factor in Hodgkin's lymphoma, but no such association has yet been established in non-Hodgkin lymphomas. Here, we have evaluated whether gender has prognostic impact on the survival of patients with B-cell non-Hodgkin lymphoma in the postrituximab era of lymphoma therapies. The study populations consisted of 217 diffuse large B-cell lymphoma (DLBCL) and 110 follicular lymphoma (FL) patients treated with immunochemotherapy. Hundred and sixty chemotherapy-treated DLBCL patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
41
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 13 publications
8
41
2
Order By: Relevance
“…To our knowledge, no studies have been performed regarding gender-related differences in BL disease biology or the impact of gender on BL prognosis. Our results contradict those achieved in diffuse large B-cell lymphoma (DLBCL), which have shown a worse prognosis for males 16 .…”
Section: Discussioncontrasting
confidence: 99%
“…To our knowledge, no studies have been performed regarding gender-related differences in BL disease biology or the impact of gender on BL prognosis. Our results contradict those achieved in diffuse large B-cell lymphoma (DLBCL), which have shown a worse prognosis for males 16 .…”
Section: Discussioncontrasting
confidence: 99%
“…[12][13][14][15] From nonrandomized comparisons, it appears that the negative impact of male gender is more pronounced in DLBCL patients treated with R-CHOP-like chemotherapy than with chemotherapy alone. 16,17 The multivariable analyses of RICOVER-60 4 show that male gender is associated with a slightly (but nonsignificantly) increased risk for an event in EFS, PFS, and OS in patients treated with CHOP chemotherapy without rituximab, but male gender evolves as a significant risk factor for EFS and PFS when rituximab is added to CHOP, demonstrating a differential effect of rituximab on the outcome of elderly female and male patients. This observation in the RICOVER-60 trial was confirmed in the other trials listed in Table 2, where elderly patients received CHOP with and without rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…This observation has been made in PTCLs in smaller series before 8,17 as well as in B-cell lymphomas. 18 IPI is, however, not likely to be optimal for risk assessment in all types of PTCLs. 17,19 In PTCL NOS, the PIT score has been suggested to be a better tool for risk stratification than the IPI.…”
Section: Blood 4 September 2014 X Volume 124 Number 10 Population-bmentioning
confidence: 99%